2007
DOI: 10.17221/754-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of barley grass as a potential source of some nutritional substances

Abstract: The relation between nutrition and health has been unequivocally established. Wrong eating habits and losses of nutritional factors during technological processing, storage, and culinary treatments can lead to the diet deficient in some nutritional factors. Barley green matter was analysed for the contents of vitamin C, total polyphenols, phenolic compounds, proteins, amino acids, and saccharides; the activity of catalase was also determined. The contents of vitamin C, total polyphenols, and ferulic acid decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
2
27
0
4
Order By: Relevance
“…Although, the amino acid levels are influenced by the condition of cultivation, such as soil, fertilizers, temperature, and so on, these high concentrations of 3 kinds of amino acid in our test were the same as those reported previously [22]. Urquhart and Joy's [23] reported that asparagic acid promotes the metabolism of aged leaves in leguminous plants such as Pisum sativum.…”
Section: Discussionsupporting
confidence: 89%
“…Although, the amino acid levels are influenced by the condition of cultivation, such as soil, fertilizers, temperature, and so on, these high concentrations of 3 kinds of amino acid in our test were the same as those reported previously [22]. Urquhart and Joy's [23] reported that asparagic acid promotes the metabolism of aged leaves in leguminous plants such as Pisum sativum.…”
Section: Discussionsupporting
confidence: 89%
“…Hydroxyl groups and their resonance stabilization effects on the phenol rings of phenolic compounds are responsible for plant antioxidant activity [30][31][32][33] . A positive correlation between antioxidant activity and the phenolic content of crude extracts has been demonstrated among different plant parts and species such as rice bran 11 , wild Indian black plums 34 , barley grass 35 , and common edible fruits 36 . In this study, Pearson correlation coefficients (R) indicated a relationship between the antioxidant activity, TPC, and TMAC of rice grass and wheatgrass juices ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…• aminokwasy: tryptofan, kwas glutaminowy, alanina, kwas asparaginowy, metionina, arginina, lizyna, cystyna, glicyna, histydyna, izoleucyna, leucyna, fenyloalanina, prolina, seryna, treonina, tyrozyna, walina, małe polipeptydy [8]; • witaminy: A, B1, B2, B3, B4, B6, B7, C, E, K [8,9,10,11]; • minerały i pierwiastki śladowe: cynk, selen, fosfor, potas, wapń, bor, chrom, kobalt, miedź, jod, żelazo, magnez, mangan, nikiel, sód, siarka [9,11]; • kwasy tłuszczowe: linolenowy i linolowy [9].…”
Section: Słowa Kluczoweunclassified
“…Tę samą korelację zaobserwowano w przypadku analizy zawartości glukozy (15,40-88,40 g/kg) i fruktozy (37,60-81,40 g/kg). Ponadto, u najmłodszych roślin odnotowano najwyższą aktywność katalazy (18,5-35,1 TSU) [8]. Przytoczone dane korespondują z wynikami wieloletnich badań Kazuhiko Kubota, który już we wczesnych latach 90.…”
Section: Jęczmień Jako żYwność Funkcjonalnaunclassified
See 1 more Smart Citation